A journey to the New World: the diary of Remember Patience Whipple : Mayflower/Plimoth Colony, 1620 (Scholastic, 1995)
Twelve-year-old Mem presents a diary account of the trip she and her family made on the Mayflower in 1620 and their first year in the New World.